Content Marketing and Engagement Marketing: Digital Actions by Footwear Companies Inspired by the Barbie Movie (Revista Brasileira de Contabilidade e Gestão, 2024)
Objective: identify content marketing and engagement marketing actions carried out on social media by footwear companies that created products inspired by the Barbie film. Method: qualitative, descriptive and netnographic research, data collection was used to analyze social networks Facebook, Instagram and the companies' website, with analysis of publications and interactions with followers in the month of July 2023, dates before and after the release of the film Barbie. Results: relevant companies in the footwear area were chosen, including Grendene (Melissa) and Calçados Piccadilly, which had a collab with the Barbie brand, and Calçados Beira Rio (brands Moleca and Vizzano), which even without the partnership used the pink color that can be associated with Barbie. Contributions: the creation of content marketing actions associated with cultural and social themes is a differentiator for brands, as customers can learn about the products and be encouraged to make purchases. However, the importance of digital content being in line with what the brand seeks as a purpose and with the chosen theme stands out, as it was possible to notice in some cases that the publications and products did not seem to be related to Barbie. It is noteworthy that partnerships with famous people and digital influencers, as occurred with Calçados Piccadilly, Moleca and Vizzano, generate digital engagement.
Keywords: content marketing; engagement marketing; Barbie movie; collab